Analisis Penyajian Laporan Keuangan Meubel Dua Saudara Kota Bengkulu - Penti Safitri; Herlin Herlin; Yudi Irawan Abi (Politeknik Raflesia Press, 2025)
ABSTACT Meubel Dua Saudara is an MSME that has not managed financial reports based on the Financial Accounting Standards for Micro, Small and Medium Enterprises. The documents prepared by Meubel Dua Saudara, Bengkulu City are made based on production process transactions. the records made include details of sales transactions, raw material inventories, equipment purchases and overall operational costs. in this case the owner does not make a complete and structured financial report post. Business Furniture of Meubel Dua Saudara, Bengkulu City produces goods when orders are requested by consumers. for employee wages issued when consumer orders have been carried out.The purpose of this study was to determine whether the presentation of the financial statements of Meubel Dua Saudara, Bengkulu City was in accordance or not in accordance with SAK EMKM 2018 with fair presentation This study uses a comparative descriptive method. data sources were obtained using primary data and secondary data. Notes The report presented by Meubel Dua Saudara, Bengkulu City is declared not in accordance with the comparison of the Financial Statements of Meubel Dua Saudara, Bengkulu City with the Financial Statements based on SAK EMEKM 2018, because it does not classify costs, revenues and all tax expenses into the form of financial statements according to the components of the Balance Sheet, Profit and Loss and notes to financial statements.